Desempenho energético do setor extrativo de minério de ferro no Brasil no período de 2011 a 2020 - Santos, Yolacir Carlos de Souza (2023)
The mining activity constitutes an important industrial sector in Brazil and, like many others, requires high energy consumption for its operations. However, the disclosure of information in this sector, regarding energy, is aggregated with that of pelletizing, which impairs the analysis of the mineral sector in a disaggregated manner. In this sense, the present study, which can be characterized as applied in nature and, in its objectives, defined as descriptive research; and in its procedure, as documentary, aimed to analyze the energy performance of the iron mining sector from 2011 to 2020. Due to the lack of disclosure of disaggregated data, primary information from the National Mining Agency obtained from the regulated sector was used, through the declaration of Annual Mining Reports. Thus, from the process of collecting and processing the individual data of each mining complex, regarding the use of diesel and electric energy, it was possible to analyze the energy consumption of the iron mining sector, as well as to estimate it in a disaggregated manner between the mining and beneficiation sectors, concluding that, in the period covered in the study, there was an increase in energy consumption (51%) and the identification that the majority of the energy expenditure derives from the use of diesel oil. By using consolidated energy performance indicators in the mineral sector, it was verified, over the study period, a tendency of increased energy required for iron ore production (33% in mining, 39% in beneficiation, and 41% in total), explained by the decrease in grades and the increase in waste-ore ratio and average transport distance, which necessitates higher energy consumption in mining and beneficiation. In addition, based on the energy consumption information, estimates of greenhouse gas emissions from the sector were made for the reported period, resulting in a 62% increase, justified by the same factors already mentioned.